Association Between Increased Homocysteine Levels and Impaired Fibrinolytic Potential: Potential Mechanism for Cardiovascular Risk - Tofler, Geoffrey H.; D’Agostino, Ralph B.; Jacques, Paul F.; Bostom, Andrew G.; Wilson, Peter W. F.; Lipinska, Izabela; Mittleman, Murray A.; Selhub, Jacob (Thrombosis and Haemostasis, 2002)
Elevated homocysteine levels increase cardiovascular risk although the mechanism is not well understood. Since thrombosis plays an important role in plaque development and acute coronary syndromes, hyperhomocysteinemia may increase risk by increasing the thrombotic potential.Hemostatic risk factors were measured in 3216 individuals (1451 men and 1765 women) free of cardiovascular disease who participated in cycle 5 of the Framingham Offspring Study. An increase in homocysteine level was associated with a rise in plasminogen activator inhibitor (PAI-1), tissue plasminogen activator (TPA) antigen, von Willebrand factor and fibrinogen level. After regression analyses adjusting for covariates, there remained significant associations between homocysteine and PAI-1 and TPA antigen.Increasing homocysteine levels are associated with impaired fibrinolytic potential, as indicated by increased PAI-1 and TPA antigen levels. These data suggest that folic acid and other homocysteine lowering therapies may decrease cardiac events through a reduction in thrombotic tendency.
Keywords: Homocysteine; cardiovascular disease; thrombosis